Presentation of lipid antigens by CD1 glycoproteins - Schiefner, André (2009)
CD1 molecules are a family of non-polymorphic, class I antigen-presenting glycoproteins, which bind and present amphiphilic lipid antigens for recognition to T cells. Two groups of CD1 molecules are involved in presentation self and foreign lipid antigens: group 1 (CD1a, CD1b and CD1c) and group 2 (CD1d). Crystal structures of CD1a, CD1b and CD1d in complex with different ligands have revealed the key principles of the lipid presentation and defined unique binding groove architectures for the individual CD1 isoforms, which enable binding and presentation of an enormous variety of lipids. Structural and biochemical insights into presentation of glycolipids by CD1d have led to the discovery of novel lipid antigens and to a broader understanding of the underlying structural and mechanistic principles of NKT cell stimulation. Some of these glycolipids show enhanced and more specific stimulatory properties and crystal structures have suggested further design strategies for elicitation of immunostimulatory compounds that may enable selective control of the secretion of regulatory T helper cytokines.